Severe late dysphagia and cause of death after concurrent chemoradiation for larynx cancer in patients eligible for RTOG 91-11. (June 2016) - Ward, Matthew C.; Adelstein, David J.; Bhateja, Priyanka; Nwizu, Tobenna I.; Scharpf, Joseph; Houston, Narcissa; Lamarre, Eric D.; Lorenz, Robert; Burkey, Brian B.; Greskovich, John F.; Koyfman, Shlomo A.
Highlights: Detailed, long-term analysis of late toxicity in larynx preservation patients. Competing risk analysis on late toxicity controlling for recurrence or death. Investigation into the factors predictive of late dysphagia. Insight into the timing and nature of late dysphagia. Summary: Purpose: The long-term results of RTOG 91-11 suggested increased deaths not attributed to larynx cancer after concomitant chemoradiotherapy (CRT) despite no apparent increase in late effects. Because the timing of events was not reported by RTOG 91-11, one possibility is that severe late dysphagia (SLD) develops beyond five years and leads to unreported treatment-related deaths. Here we explore the timing of SLD after CRT. Methods: Patients who would have met eligibility criteria for RTOG 91-11 and were treated with CRT between 1993 and 2013 were identified. Events occurring beyond 3 months after treatment and suggestive of SLD were recorded including esophageal stricture dilations, hospital admissions for aspiration pneumonia or feeding-tube insertion. Feeding-tube dependence beyond one year was also considered SLD. The cumulative incidence of SLD and its components was quantified using Gray's competing risk analysis with recurrence or death considered competing risks. Results: Eighty-four patients were included with a median follow-up of 43 months. The 5-year overall survival was 70% (95% CI 58–80%). No death was directly a result of treatment-induced late dysphagia. The 5-year incidence of SLD was 26.5%. While 15 of 18 (83%) first stricture dilations occurred within 5 years after CRT, 3 of 5 (60%) aspiration admissions and 5 of 8 late feeding tube insertions occurred beyond five years from CRT. Conclusions: SLD is common after CRT for larynx cancer and can occur beyond 5 years from the end of treatment, emphasizing the importance of survivorship follow-up. Despite the incidence of SLD, death related to dysphagia is uncommon.